Analisis atribut kualitas jasa layanan terhadap kepuasan anggota pada KPRI "KOPPENDA" Kabupaten Sleman - Santoso, Fajar (Entrepreneurship Bisnis Manajemen Akuntansi (E-BISMA), 2021)
Service quality can be relied upon as one of the competitive advantages in increasingly fierce business competition. Excellent service quality is proven to be able to create consumer loyalty, because excellent quality is often synonymous with customer satisfaction; and in the end, through customer satisfaction the company will gain long-term profits.The purpose of this research is to find out: (1) How is the level of member satisfaction with the service quality of KPRI "KOPPENDA" Kab. Klaten; (2) What is the most dominant variable in influencing the level of member satisfaction with the service quality of KPRI "KOPPENDA" Kab. Klaten.Based on the results of the study, it can be concluded that: (1) The level of member satisfaction with the service quality of KPRI "KOPPENDA" Kab. Klaten is low; (2) The most dominant variable in influencing the level of member satisfaction with the service quality of KPRI "KOPPENDA" Kab. Klaten is Reliability